2010
DOI: 10.1017/s0952523810000246
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of alpha 7 nicotinic acetylcholine receptor expression in retinal pigment epithelial cells

Abstract: Some evidence suggests that retinal pigment epithelium (RPE) can express nicotinic acetylcholine receptors (nAChRs) as described for other epithelial cells, where nAChRs have been involved in processes such as cell development, cell death, cell migration, and angiogenesis. This study is designed to determine the expression and activity of a7 nAChRs in RPE cells. Reverse transcriptase (RT)-PCR was performed to test the expression of nicotinic a7 subunit in bovine RPE cells. Protein expression was determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
(71 reference statements)
0
15
0
Order By: Relevance
“…Several reports have confirmed that RPE expresses α7 nAChR [10], [24]. Thus, we speculated that acetylcholine might also be enriched in photoreceptor OS.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Several reports have confirmed that RPE expresses α7 nAChR [10], [24]. Thus, we speculated that acetylcholine might also be enriched in photoreceptor OS.…”
Section: Resultsmentioning
confidence: 57%
“…Although nAChRs act as signal transducers in neurons [6], they have different roles in nonexcitable cells where they contribute to homeostasis [7][9]. Maneu et al [10] investigated the expression of α7 nAChR in retinal pigment epithelium (RPE) cells, and reported that immunoreactivity of α7 nAChR was observed in RPE cells, especially in the apical surface of RPE cells adjacent to photoreceptor outer segments (OS). In contrast, photoreceptor OS showed no α7 nAChR immunoreactivity.…”
Section: Introductionmentioning
confidence: 99%
“…We were able to show that the resistance of the RPE against nicotine is not limited to cell lines but holds true for primary RPE cells, and is valid after even after prolonged exhibition (up to 1 week). The authors suggested the resistance of ARPE-19 cells to be explained by an absence of nicotine receptors on these; however, RPE cells do express nicotinic acetylcholine receptors, and as such are able to specifically respond to nicotine [23,24].…”
Section: Discussionmentioning
confidence: 97%
“…This result would dispute the possibility that BrdU positive cells are initiated from RGCs that contain α7 nAChRs (Thompson et al, 2006). However, it does not rule out the possibility that the α7 nAChR agonist binds to receptors in the retinal pigment epithelium (Maneu et al, 2010; Matsumoto et al, 2012; Fuhrmann et al, 2014), which then secrete unknown signaling factors that initiates the division of Müller glia. Further experiments are required to examine this possibility.…”
Section: Discussionmentioning
confidence: 99%